Water Reuse: From Ancient to Modern Times and the Future - Angelakis, Andreas N.; Asano, Takashi; Bahri, Akissa; Jimenez, Blanca E.; Tchobanoglous, George (Frontiers in Environmental Science, 2018)
Domestic wastewater (sewage) has been used for irrigation and aquaculture since the Bronze Age (ca. 3,200-1,100 BC) by prehistoric civilizations (e.g. Chinese, Egyptian, Indus Valley, Mesopotamian, and Minoan). In historic times (ca. 1,000 BC-330 AD), wastewater was disposed of or used for irrigation and fertilization purposes by the Greek civilization and later by the Romans in areas surrounding cities (e.g. Athens and Rome). In more recent history, the practice of land application of wastewater for disposal and agricultural use was utilized first in European cities and later in USA. Today, the planning and implementation of water reclamation and reuse projects is occurring throughout the world. Recycled water is now used for almost any purpose including potable use. This paper provides a brief overview of the evolution of water reuse over the last ca. 5,000 years. Understanding the practices and solutions of the past, provides a lens with which to view present and future challenges in a highly-urbanized world.